EDUKASI INKONTINENSIA URIN PADA WANITA DI RT 03 RW 01 GRATI TUNON KECAMATAN GRATI KABUPATEN PASURUAN - Wardani, Alifiyah Lintang (Jurnal Pengabdiaan Masyarakat Kasih (JPMK), 2026)
Urinary incontinence is a condition characterized by the involuntary leakage of urine in amounts and at frequencies that are difficult to control. Urinary incontinence is a common complaint that is often overlooked by the public because it is considered a normal part of aging. One effective therapy for urinary incontinence in women is Kegel exercises. Therefore, it is important to conduct educational activities, particularly among women in the mothers’ group of RT 03 RW 01 Grati Tunon, Grati Subdistrict, Pasuruan Regency. This activity is expected to improve understanding of urinary incontinence as well as how to prevent and manage it. Educational leaflets were distributed to all participants after the pre-test, followed by the delivery of educational material through lectures and demonstrations of Kegel exercises. The closing session included a post-test and a question-and-answer session. The evaluation showed an increase in knowledge among the 10 participants present regarding urinary incontinence and Kegel exercises, indicating that this activity had a positive impact on them.